2020
DOI: 10.1021/acs.jpcb.0c06607
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Role of Tetraethylammonium in the Silicate Condensation Reaction from Ab Initio Molecular Dynamics Simulations

Abstract: The understanding of the formation of silicate oligomers in the initial stage of zeolite synthesis is important. The use of organic structure-directing agents (OSDAs) is known to be a key factor in the formation of different silicate species and the final zeolite structure. For example, tetraethylammonium ion (TEA + ) is a commonly used organic template for zeolite synthesis. In this study, ab initio molecular dynamics (AIMD) simulation is used to provide an unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 67 publications
2
15
0
Order By: Relevance
“…To better understand the influence of NaI on the SiO 2 /Al 2 O 3 ratio of zeolites, DFT calculations were performed to explore the thermodynamics and kinetics of the Si–O–Si and Si–O–Al bond formation in the presence of NaI (computational details are shown in the ESI†). Herein, based on the previous calculations for zeolite synthesis, 49–52 Si(OH) 4 and Al(OH) 4 Na monomers, as the basic structural units of zeolites, were selected to form Si–O–Si or Si–O–Al bonds by condensation of Si(OH) 4 with either Si(OH) 4 or Al(OH) 4 Na, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To better understand the influence of NaI on the SiO 2 /Al 2 O 3 ratio of zeolites, DFT calculations were performed to explore the thermodynamics and kinetics of the Si–O–Si and Si–O–Al bond formation in the presence of NaI (computational details are shown in the ESI†). Herein, based on the previous calculations for zeolite synthesis, 49–52 Si(OH) 4 and Al(OH) 4 Na monomers, as the basic structural units of zeolites, were selected to form Si–O–Si or Si–O–Al bonds by condensation of Si(OH) 4 with either Si(OH) 4 or Al(OH) 4 Na, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…29 Mai et al investigated the role of tetraethylammonium ion on zeolite synthesis. 30 They observed the energy barrier of 63 kJ mol −1 (15.06 kcal mol −1 ). Our study shows a similar range of energy barriers for condensation between monocalcium silicate and orthosilicate ion.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that since the above-mentioned studies are AIMD based, specific orientation of the molecules is not possible and thereby the above studies present an overall/global effect of the reaction without a much detailed focus on different possible and individual reaction pathways. The presence of organic tetraalkylammonium ions like methyl and ethyl on silicate condensation have also been studied 30 in which it had been demonstrated that TEA (tetraethylammonium ion) provides a favourable environment for the formation of a 3-ring over a 4-ring structure. Here it should be noted that the cations in the above studies are only monovalent ions (H + , Li + , Na + , NH 4 + or organic tetraalkylammonium ions like TMA, TEA, TPA, or TBA) which behave differently depending upon their bulkiness or coordination with oxygen or surrounding water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…A number of groups [53][54][55][56][57][58][59][60][61][62] studied the silicate/aluminate condensation and nucleation starting from the reaction between Si(OH) 4 and Si(OH) 3 O À monomers, where the anion attacks the neutral species to form an intermediate structure containing a 5-fold coordinated Si center. The initial dimerization reaction appears fast since the reaction barrier is as low as 0.36 eV from DFT calculations, but the continuous polymerization is sensitive to the solution conditions.…”
Section: Zeolite Formationmentioning
confidence: 99%